A Study of the Relationship Between Corporate Governance and Organizational Performance - Rupak Karmakar; Uttam Kumar Dutta (Journal of Corporate Governance Research, 2024)
This study examined whether the relationship between corporate governance and organizational performance exists or not. Conceptual framework has been developed to measure with the help of questionnaire data, which has been collected from different organizations. Factor analysis has been used for the purpose of this study. From the data analysis, it has been shown that corporate governance and organizational performance relation are at high level and corporate governance significantly impacts on organizational performance.